The Impact of Public Debt on Economic Growth In European Union Countries - Alin-Vasile STRĂCHINARU (Communications of International Proceedings, 2022)
The paper analyzes the paradoxical character that defines the relation between the sharp rise in the level of the public debt in the last decades in antithesis with the growth and, implicitly, the economic development of the member states of the European Union. The aim of this research is to capture the impact of public debt on economic growth in the Member States of the European Union, with an annual frequency, for the period 2005 - 2019, using a Vector Autoregression Model. The results of the study show a causal relationship between them, with an inertia in both the evolution of public debt and economic growth, reflected in an inversely proportional relationship. The importance of this topic consist in the decrease of public debt may contributed to an economic growth and, so, a use of resources, obtained through loans and investments and respectively the decrease of public debt may contributed to an increase of GDP index.
Keywords: Economic Growth; Euro Area; Public Debt; Vector Autoregression Model